2000
DOI: 10.1097/00004714-200008000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cytochrome P450 2D6 Modifies Codeine Abuse Liability

Abstract: Oral codeine preparations, widely used for analgesia and cough suppression, are abused by some individuals for their mood-altering properties. The enzymatic O-demethylation of codeine is catalyzed by cytochrome P450 2D6 (CYP2D6), leading to the production of metabolites (morphine, morphine-6-glucuronide) that are pharmacologically more potent than codeine. A placebo-controlled, single-blind study was conducted to characterize the subjective effects of codeine associated with abuse liability and to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…72,73 In man, the concomitant administration of codeine and quinidine, a CYP2D6 inhibitor that does not cross the blood--brain barrier and therefore only affects hepatic function, still produces the central pharmacological effects of morphine, suggesting the existence of a brain-based metabolism of codeine to morphine. 74 Brain-specific drug metabolism has also been demonstrated for other CYP450 enzymes such as CYP2B6, which can be induced by nicotine. 75 Propofol is an anesthetic agent whose effect on sleeping times was increased by locally inhibiting its homolog CYP2B in the brain of rats.…”
Section: Polymorphic Dmes In the Brainmentioning
confidence: 99%
“…72,73 In man, the concomitant administration of codeine and quinidine, a CYP2D6 inhibitor that does not cross the blood--brain barrier and therefore only affects hepatic function, still produces the central pharmacological effects of morphine, suggesting the existence of a brain-based metabolism of codeine to morphine. 74 Brain-specific drug metabolism has also been demonstrated for other CYP450 enzymes such as CYP2B6, which can be induced by nicotine. 75 Propofol is an anesthetic agent whose effect on sleeping times was increased by locally inhibiting its homolog CYP2B in the brain of rats.…”
Section: Polymorphic Dmes In the Brainmentioning
confidence: 99%
“…Some of these variants increase metabolism of these drugs into their more potent metabolites, whereas others decrease metabolism. The analgesic potency and abuse liability of opioid medications may, therefore, be influenced by variants in this gene (Sindrup et al, 1991(Sindrup et al, , 1993Kathiramalainathan et al, 2000). Tyndale et al (1997) reported that no subjects meeting DSM-IV criteria for oral opioid dependence had either of the defective mutant alleles CYP2D6*3 or CYP2D6*4 which reduce metabolism compared with control and multidrug-dependent individuals whose frequency for these alleles did not differ from that of previously reported Caucasian control populations.…”
Section: A Metabolism/biotransformation Of Opiates and Other Opioidsmentioning
confidence: 99%
“…Tyndale et al (1997) reported that no subjects meeting DSM-IV criteria for oral opioid dependence had either of the defective mutant alleles CYP2D6*3 or CYP2D6*4 which reduce metabolism compared with control and multidrug-dependent individuals whose frequency for these alleles did not differ from that of previously reported Caucasian control populations. Pharmacological inhibition of CYP2D6 with fluoxetine or quinidine, which significantly reduces the formation OPIATE AND COCAINE ADDICTION: GENETICS AND PHARMACOGENOMICS of morphine following codeine administration (Kathiramalainathan et al, 2000;Romach et al, 2000), however, failed to reduce daily codeine intake in a small cohort of codeine addicts (Fernandes et al, 2002). The effect of CYP2D6 alleles resulting in low versus ultrarapid metabolism has been investigated in methadone-maintained subjects.…”
Section: A Metabolism/biotransformation Of Opiates and Other Opioidsmentioning
confidence: 99%
“…Despite the benefi ts of once-daily, supervised maintenance treatment with slow-release morphine suggested by our study, consideration must be given to the possible impact of cytochrome P 450 induction, which leads to accelerated elimination of morphine [32] . The pharmacokinetics of opioids is known to be affected by pregnancy, as well as by the co-administration of certain other substances that interfere with cytochrome P 450 -induced metabolism [33,34] .…”
Section: Discussionmentioning
confidence: 93%